CAPITAL COMPARISON OF CANDIDATES FROM POLITICAL DYNASTIES IN THE 2020 MAYORAL AND DEPUTY MAYORAL ELECTION IN INDONESIA - Sadiyatunnimah, Siti (Universitas Nasional, 2021)
This study was conducted to compare the capital owned by candidates from political dynasties in the 2020 mayor and deputy mayor elections and make a generalization about which capital turns out to be the most influential in the election. The study is a comparative research which uses the Large-N, a method that compares cases in a broad area and a large number, with 28 candidates from political dynasties as the objects. The conclusion of this study is that the dynasties owned by candidates do not seem to mean much in the 2020 mayor and deputy mayor elections. The victories of candidates from political dynasties were influenced by various combinations of capital. No capital is more influential than other capital because ownership of capital will not mean much if the candidate does not have a good enough strategy in using that capital to attract voters.